2017
DOI: 10.1093/ejo/cjx049
|View full text |Cite
|
Sign up to set email alerts
|

Association between severity of hypodontia and cephalometric skeletal patterns: a retrospective study

Abstract: The white Caucasian group followed a pattern that has previously been reported in other studies. For Black-British and Arabian/Indian groups' findings were inconsistent and no specific pattern emerged for different degrees of hypodontia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Skeletal, Incisor Angulations, and Soft Tissue Changes Associated with Hypodontia It was found by several studies that patients with tooth agenesis had a different craniofacial pattern when compared with patients with a normal number of teeth, [11][12][13][14][15][16] but few studies have investigated the effect of the distribution of congenitally missing teeth on the craniofacial morphology. [12][13][14][15][16][17] According to Endo et al, 17 an anterior and posterior hypodontia exerted a similar pattern on the craniofacial structures. However, skeletal and dental changes were more remarkable in patients having both anterior and posterior congenitally missing teeth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal, Incisor Angulations, and Soft Tissue Changes Associated with Hypodontia It was found by several studies that patients with tooth agenesis had a different craniofacial pattern when compared with patients with a normal number of teeth, [11][12][13][14][15][16] but few studies have investigated the effect of the distribution of congenitally missing teeth on the craniofacial morphology. [12][13][14][15][16][17] According to Endo et al, 17 an anterior and posterior hypodontia exerted a similar pattern on the craniofacial structures. However, skeletal and dental changes were more remarkable in patients having both anterior and posterior congenitally missing teeth.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] This decrease in the lower face height can be ascribed to the anterior rotation of the mandible resulting from a smaller number of teeth and, thus, less support. 11,15 Some previous studies have reported a reduction in the length of the maxillary and mandibular alveolar bone in severe hypodontia. 14,16 However, these findings contrast other investigations which showed no reduction in the maxillary and mandibular alveolar bone height in mild or severe forms of hypodontia.…”
Section: Resultsmentioning
confidence: 99%
“…Misewska et al showed statistically significant retrognathic mandible (reduced SNB angle) [18]. Taju et al obtained results demonstrating different effects of agenesis on the SNB angle value, depending on the ethnic group; they observed both a reduction and no effects of missing tooth buds on a retrusive position of the B point [21]. In the studies by Yüksel and Üçem, the mandible was more protrusive (a greater SNB angle) in the case of bilateral agenesis in the posterior segment than unilateral in the anterior and posterior segments and in the control group, and bilateral agenesis in the anterior segment than unilateral agenesis in the anterior segment.…”
Section: Discussionmentioning
confidence: 98%
“…As the number of missing teeth increases (more than six), these patterns become more prominent. 8 Patients with hypodontia may present at early mixed dentition, late mixed/early permanent and late permanent dentition. Treatment planning for mixed dentition includes prevention and reassurance, removable dentures/overdentures for psychological and functional reasons, composite build ups to improve aesthetics of microdonts, simple orthodontic space closures and schematic extractions of retained primary teeth to guide permanent tooth eruptions.…”
Section: Introductionmentioning
confidence: 99%